Exploring urinary incontinence in hospitalised older women: A mixed methods investigation of prevalence and nurse perspectives - Isobel McMillan; Liz Doxford-Hook; Julie Wood; Yu Fu; Linda McGowan; Heather Iles-Smith (Women's Health)
Background: Approximately 40% of older women in the community report experiencing urinary incontinence (UI); prevalence within secondary care is unknown. Illness, comorbidities, and hospital environments are likely to lead to higher prevalence. Objectives: This study aimed to establish UI prevalence in older women admitted to hospitals and understand the views and knowledge of ward nurses in relation to older women’s UI. Design: An explanatory mixed methods study was conducted including a retrospective study of women ⩾55 years admitted to a large NHS hospital and qualitative interviews with nurses to gain an understanding of views, knowledge and perceptions of women’s UI and related care. Method: UI prevalence was determined using the nursing assessment (elimination) and International Classification of Diseases 10th Revision (ICD-10) codes for women ⩾55 years admitted to the hospital (November 2019 to February 2020); continence and demographic electronic patient care records data were extracted. Twenty ward nurses participated in interviews to explore views, knowledge and perceptions of UI care. Results: 11.0% ( n  = 631) of the cohort (5,757) were recorded as having UI. Nurse interviews revealed six themes: (1) Normalisation and misconceptions of UI: nurses believed UI could not be improved, (2) limited knowledge and training: nurses expressed limited UI knowledge and a training need, (3) pad culture: continence pad use was high, (4) barriers to care: staffing issues were expressed as problematic, (5) UI under-reporting: nurses only categorised women with complete UI and others as “having an accident”, (6) catheter use in relation to UI: catheters were reported as a last resort. Conclusion: As community UI prevalence is 40%, our results (11%) suggest that UI is being underreported. Qualitative findings suggest that nurses have limited knowledge and training on continence care and under-report based on UI misconceptions. Our results suggest that ward nurses require dedicated UI training based on older women’s needs.